Bankruptcy Prediction Analysis Of Retail Companies Affected by Israeli Boycott Using Altman's Z-Score and Springate - Sofia Lazura; Rahmat Daim Harahap; Muhammad Syahbudi (LP2M IAIN Palopo, 2025)
This study aims to analyze the potential bankruptcy of retail sub-sector companies affected by the Israeli boycott listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024 using the Altman Z-Score and Springate models. By applying both prediction models and computing financial ratios from the companies' financial statements, this study employs a qualitative approach to evaluate the likelihood of bankruptcy. According to the findings, the Springate model has an accuracy rate of 50% with a 50% mistake rate, whereas the Altman Z-Score model has a higher accuracy rate of 75% with a 25% error rate. The quantity and kind of financial ratios employed, as well as the threshold values that each model applies, affect the variations in prediction outcomes. According to the results, the Altman Z-Score model is better suited to forecast bankruptcy in retail businesses impacted by the boycott. Businesses can use this analysis's insightful findings to identify financial issues early and take proactive steps to preserve their viability. This research contributes by providing useful insights for investors, companies, and policymakers to anticipate financial distress and make better strategic decisions in the retail sector.